Pengaruh Aromaterapi Lavender terhadap Tingkat Kecemasan Pasien Pra-Operatif dengan Anestesi Umum di RS X - Sunita Sinaga; Hery Prambudi; Qodri , Qodri; Ruby Satria Nugraha; Ani Haryani (Yayasan Literasi Sains Indonesia, 2024)
Preoperative anxiety is an adaptive response to stress before surgery. This condition not only affects the patient's psychological well-being but can also influence physiological parameters such as blood pressure, heart rate, and stress hormone levels, which may indirectly increase the risk of intraoperative and postoperative complications. Various interventions have been developed to reduce preoperative anxiety, both pharmacologically and non-pharmacologically. Non-pharmacological approaches such as aromatherapy, music therapy, and acupuncture are increasingly used as alternative treatments. The purpose of administering lavender aromatherapy in this study was to reduce preoperative anxiety in patients undergoing general anesthesia and to minimize postoperative side effects. A quasi-experimental study with a pretest-posttest design without a control group was conducted on 40 patients aged 25–45 years undergoing elective surgery at Hospital X. Aromatherapy was administered by inhalation of five drops of lavender essential oil for 15 minutes. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after the intervention. Data analysis was performed using the Wilcoxon Signed-Rank test, as the data were not normally distributed. The results showed a significant reduction in anxiety levels after the administration of aromatherapy (p < 0.05), indicating that lavender inhalation aromatherapy is effective in reducing preoperative anxiety and can be used as a complementary therapy.